Succession of soil microbial community in a developing mid-channel bar: The role of environmental disturbance and plant community - Ye, Fei; Hong, Yiguo; Wu, Jiapeng; Yi, Xuemei; Op den Camp, Huub J. M.; Moore, Selina Sterup; Vamerali, Teofilo; Wang, Yu (Frontiers in Microbiology, 2022)
Succession of microbial and plant communities is crucial for the development and the stability of soil ecological functions. The relative role of plant communities and environmental disturbance in shaping the microbial community in a newly established habitat remains unclear. In this study, a mid-channel bar (MCB) exposed to an environmental disturbance gradient in the Yangtze River was studied to explore the effects of such disturbance and plant community traits on the succession of the soil microbial community. Bulk and rhizospheric soils were collected from the MCB and classified according to their level of exposure to environmental disturbance: head, central and tail. These subsequently underwent high-throughput sequencing and interdomain ecological network (IDEN) analysis to identify and characterize the predominant microbial groups present in the soils at each disturbance level. Furthermore, at each site, the presence and distribution of the plant community was also noted. The present study demonstrated that both bulk soil nutrients and plant community exhibited significant spatial distribution dependent on the level of disturbance and this influenced the composition of the microbial community. In less eroded parts of the MCB, i.e., the central, nutrients accumulated, promoting growths of plants. This in turn encouraged a more diverse microbial community, dominated by the bacterial genus Pseudarthrobacter. Plant showed a stronger association with bulk soil microbial communities compared to rhizosphere soil microbial communities. Particularly, Triarrhena sacchariflora and Hemarthria altissima, present in sites of low disturbance, exhibiting a more extensive plant-microbe association. They thus played a key role in shaping the soil microbial community. In general, however, plant species did not directly determine the composition of the bacterial community, but instead altered the nutritive state of the soil to promote microbial growth. Such findings are of significant value for conservation practices of newly formed ecosystems, which requires an integrated understanding of the role of environmental disturbance and plants on soil microbial community assemblage.